Analysis of the Influence of Social Media Engagement, Personalization Quality, and Service Quality on Digital Brand Loyalty of Online Retail Customers - Rio Haribowo; Sukma Irdiana; Ida Ayu Trisna Wijayanthi; Sofia Maulida; Imam Jayanto; Fahrina Mustafa (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The primary aim of the research is to measure how the communication via social media, the degree of personalization, and the service rendered through the internet affect the customers’ loyalty toward the brand in the context of online retail digital loyalty, along with the customer interaction and personalization quality. The site of the study is selected based on the cutting-edge rivalry among online retailers and the necessity for brand loyalty to be a decisive factor in the digital companies' survival. A quantitative explanatory research design has been applied with 250 online retail customer respondents who are selected through purposive sampling method. The data gathering is carried out using a questionnaire based on a five-point Likert scale and multiple linear regression is the method used for analyzing the data. The study findings confirm that social media interactions, personalization quality, and service have a significantly large positive effect on digital brand loyalty of the customers. The research, however, presents the online retail sector with an opportunity for a strategic advantage in marketing, service personalization, and quality improvements for building up a long-lasting brand loyalty.